A study on accounting curricular and future accounting graduates / Halil Paino and Mohd Soffi Puteh - Paino, Halil; Puteh, Mohd Soffi (UiTM Pahang & UPENA, 2006)
The Faculty of Accountancy plays an important role in the education of accountants beyond the baccalaureate degree. Looking at the advertisements in the newspapers and the way the accounting graduates are being readily absorbed into the job market, one gets the feeling that there is a big demand for accounting graduates and accountants. In addition, the employers want and expect their new – entry professionals to be equipped with all relevant skills and knowledge. In view of the current rapid development in business and technology around the world, an assessment on accounting programmes in this country is needed. This research was, therefore, undertaken to address the current state of accounting education and to find out the perceptions of students, academics, employers and practitioners on the matters reflecting the needs in enhancing accounting education. The findings suggest a combination of intellectual, personal attributes and future competencies needed by all accounting graduates to be included in the curriculum.